2020
DOI: 10.1021/acs.jafc.0c05943
|View full text |Cite
|
Sign up to set email alerts
|

Poria cocos Polysaccharides Alleviates Chronic Nonbacterial Prostatitis by Preventing Oxidative Stress, Regulating Hormone Production, Modifying Gut Microbiota, and Remodeling the DNA Methylome

Abstract: Chronic nonbacterial prostatitis (CNP) is a common male disease with high incidence and low cure rate. This study aims to investigate the anti-CNP potential of Poria cocos polysaccharides (PPs) in a λ-carrageenan-induced CNP rat model. Results showed that PPs exerted anti-CNP functions by reducing the prostate weight and prostate index as well as the level of C-reactive protein (CRP) and pro-inflammatory cytokines (TNF-α and IL-1β). Further analysis on sex hormones revealed that PPs could favor CNP alleviation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Antiasthmatic effects of YTE observed in this study were supported by various previous studies [11,12,16]. e crude herbs that make up YTE have been shown to have antiinflammatory and antioxidant properties in various research studies [12][13][14][15]. Furthermore, we characterized the active components in YTE using HPLC.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Antiasthmatic effects of YTE observed in this study were supported by various previous studies [11,12,16]. e crude herbs that make up YTE have been shown to have antiinflammatory and antioxidant properties in various research studies [12][13][14][15]. Furthermore, we characterized the active components in YTE using HPLC.…”
Section: Discussionsupporting
confidence: 85%
“…Yijin-tang has been shown to exhibit curative effects against gastric injury induced by ethanol through enhancement of antioxidant status. In addition, the crude herbs that constitute Yijin-tang have strong antioxidant properties [12][13][14][15]. Owing to this, we predicted that Yijintang would be effective in treating asthma.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] A growing number of studies have recognized that plant polysaccharides are natural flora regulators, and they can enhance systemic immune function by regulating gut microbiota. [14][15][16] Astragalus polysaccharides (APS), the main effective component of Astragalus membranaceus, can enhance immune function and inhibit tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…AGA is positively associated with immune modulation and inflammation, and thus, anti-inflammatory agents can be used to treat the condition [42]. In previous studies, PC was found to reduce the mRNA expressions of TNF-α and IL-6 and to combat chronic nonbacterial prostatitis (a male disease) and arteriosclerosis [39,43]. Chronic nonbacterial prostatitis can be relieved by regulating testosterone, DHT, and 17β-estradiol levels [43].…”
Section: Discussionmentioning
confidence: 99%